Research priorities for mitochondrial disorders: Current landscape and patient and professional views. Issue 4 (31st May 2022) - Thomas, Rhys H.; Hunter, Amy; Butterworth, Lyndsey; Feeney, Catherine; Graves, Tracey D.; Holmes, Sarah; Hossain, Pushpa; Lowndes, Jo; Sharpe, Jenny; Upadhyaya, Sheela; Varhaug, Kristin N.; Votruba, Marcela; et al.
Abstract: Primary mitochondrial disorders encompass a wide range of clinical presentations and a spectrum of severity. They currently lack effective disease‐modifying therapies and have a high mortality and morbidity rate. It is therefore essential to know that competitively funded research designed by academics meets the core needs of people with mitochondrial disorders and their clinicians. Priority setting partnerships are an established collaborative methodology that brings patients, carers and families, charity representatives and clinicians together to try to establish the most pressing and unanswered research priorities for a particular disease. We developed a web‐based questionnaire, requesting all patients affected by primary mitochondrial disease, their carers and clinicians to pose their research questions. This yielded 709 questions from 147 participants. These were grouped into overarching themes including basic biology, causation, health services, clinical management, social impacts, prognosis, prevention, symptoms, treatment and psychological impact. Following the removal of "answered questions", the process resulted in a list of 42 discrete, answerable questions. This was further refined by web‐based ranking by the community to 24 questions. These were debated at a face‐to‐face workshop attended by a diverse range of patients, carers, charity representatives and clinicians to create a definitive "Top 10 of unanswered research questions for primary mitochondrial disorders". These Top 10 questions related to understanding biological processes, including triggers of disease onset, mechanisms underlying progression and reasons for differential symptoms between individuals with identical genetic mutations; new treatments; biomarker discovery; psychological support and optimal management of stroke‐like episodes and fatigue.